Revolutionizing Lead (II) Ion Removal from Water: Eco-Friendly Composite Film with Graphene Oxide and Bacterial Cellulose - Nguyen, Tuan Anh (Trends in Sciences, 2025)
Bacterial cellulose (BC), produced through the natural fermentation of coconut water, is composed of 1-dimensional (1D) nanofibers with remarkable mechanical properties. Within this study, a novel composite material was synthesized by combining bacterial cellulose with graphene oxide (GO) to create an eco-friendly and highly effective adsorbent for the removal of Pb(II) heavy metal ions from water. The research employed a systematic methodology, including the synthesis of BC/GO composites with varying fabrication ratios. Advanced characterization techniques were utilized to analyze the properties of the composites: scanning electron microscopy (SEM) for structural observation, thermogravimetric analysis (TGA) for thermal stability assessment, Fourier-transform infrared spectroscopy (FTIR) for chemical bonding identification, and atomic absorption spectrophotometry (AAS) for quantifying Pb(II) ion adsorption capacity. The results demonstrated the successful fabrication of BC/GO composites featuring a nanostructure with intertwined BC nanofibers and GO layers. These composites exhibited impressive mechanical strength and a high adsorption efficiency for Pb(II) ions, exceeding 90 % at an optimal pH of 5. Notably, the BC/GO composite with a fabrication ratio of 1:7 showed superior structural and thermal properties, with a maximum adsorption capacity of 315.5 mg g⁻¹. The findings highlight the potential of BC/GO composites as high-performance, eco-friendly adsorbents for heavy metal removal. The combination of BC and GO provides a robust material with excellent adsorption capacity and mechanical properties, paving the way for future applications in water purification technologies. This revised abstract is structured to ensure clarity and logical flow, presenting the study’s key aspects concisely. The methodology has been clearly described, and typographical issues have been corrected. HIGHLIGHTS A novel eco-friendly composite film was successfully fabricated by integrating bacterial cellulose (BC) with graphene oxide (GO) for Pb(II) ion removal. The BC/GO composites exhibited a highly porous nanostructure, strong mechanical strength, and enhanced thermal stability. The optimal composite ratio (BC:GO = 1:7) achieved a maximum Pb(II) adsorption capacity of 315.5 mg g⁻¹ at pH 5. Advanced characterization techniques (SEM, FTIR, TGA, AAS) confirmed the structural integration and adsorption efficiency of the composites. The study demonstrates the potential of BC/GO composites as sustainable and high-performance adsorbents for heavy metal removal from water. GRAPHICAL ABSTRACT